Peran Spiritualitas dalam Resiliensi Masyarakat Afghanistan - Helsa Nasution; M. Agung Rahmadi; Luthfiah Mawar; Nurzahara Sihombing (Pusat Riset dan Inovasi Nasional, 2025)
Through a systematic review and meta-analysis, this research investigates the relationship between spirituality and psychological resilience in the Afghan population. Of the 1,247 identified studies, 47 (N=12,468) met the inclusion criteria. The results of the random-effects model analysis confirm a strong positive correlation between spirituality and psychological resilience (r = 0.64, 95% CI [0.58, 0.70], p < .001). Furthermore, there is significant heterogeneity among studies (I² = 76.3%, Q = 182.45, p < .001). Additionally, moderator analysis reveals that the effect of spirituality on resilience is significantly stronger in Afghan groups experiencing war trauma (β = 0.72) compared to non-traumatized groups (β = 0.51). Meta-regression results indicate that daily spiritual practice accounts for 43.2% of the total variance in psychological resilience among the Afghan community. In comparison to the findings of Salsman et al. (2015) and Schwalm et al. (2022), which reported a moderate correlation between the two variables (r = 0.45-0.52), this study has reinforced the presence of a stronger effect of spirituality on resilience in the context of prolonged conflict, presenting a novel contribution. Lastly, the mediation analysis indicates that the sense of meaning in life mediates the spirituality-resilience relationship in Afghanistan by 67.8% (95% CI [61.2, 74.5]). This research expands upon the findings of Meichenbaum (2008) by identifying specific mechanisms that explain the protective role of spirituality in the context of collective trauma in Afghanistan. Thus, these findings can universally serve as an empirical foundation for developing spirituality-based interventions for trauma recovery in communities affected by prolonged conflict.